The role of vascular biomarkers for primary and secondary prevention. A position paper from the European Society of Cardiology Working Group on peripheral circulation: Endorsed by the Association for Research into Arterial Structure and Physiology (ARTERY) Society. Issue 2 (August 2015) - Vlachopoulos, Charalambos; Xaplanteris, Panagiotis; Aboyans, Victor; Brodmann, Marianne; Cífková, Renata; Cosentino, Francesco; De Carlo, Marco; Gallino, Augusto; Landmesser, Ulf; Laurent, Stéphane; Lekakis, John; Mikhailidis, Dimitri P.; et al.
Abstract: While risk scores are invaluable tools for adapted preventive strategies, a significant gap exists between predicted and actual event rates. Additional tools to further stratify the risk of patients at an individual level are biomarkers. A surrogate endpoint is a biomarker that is intended as a substitute for a clinical endpoint. In order to be considered as a surrogate endpoint of cardiovascular events, a biomarker should satisfy several criteria, such as proof of concept, prospective validation, incremental value, clinical utility, clinical outcomes, cost-effectiveness, ease of use, methodological consensus, and reference values. We scrutinized the role of peripheral (i.e. not related to coronary circulation) noninvasive vascular biomarkers for primary and secondary cardiovascular disease prevention. Most of the biomarkers examined fit within the concept of early vascular aging. Biomarkers that fulfill most of the criteria and, therefore, are close to being considered a clinical surrogate endpoint are carotid ultrasonography, ankle-brachial index and carotid-femoral pulse wave velocity; biomarkers that fulfill some, but not all of the criteria are brachial ankle pulse wave velocity, central haemodynamics/wave reflections and C-reactive protein; biomarkers that do no not at present fulfill essential criteria are flow-mediated dilation, endothelial peripheral arterial tonometry, oxidized LDL and dysfunctional HDL. Nevertheless, it is still unclear whether a specific vascular biomarker is overly superior. A prospective study in which all vascular biomarkers are measured is still lacking. In selected cases, the combined assessment of more than one biomarker may be required. Highlights: Risk scores are used in clinical decision-making but can under- or overestimate risk. Biomarkers can further stratify the risk of patients at an individual level. Biomarkers may prevent the occurrence of clinical disease by timely treatment. Nine criteria should be met for a biomarker to be a surrogate endpoint. Carotid ultrasonography, ABI and cfPWV fulfill most of the criteria.